2001
DOI: 10.4141/p00-129
|View full text |Cite
|
Sign up to set email alerts
|

Effect of post-harvest management on seed production of creeping red fescue, tall fescue, and Kentucky bluegrass in the Peace River region of north-western Canada

Abstract: Fairey, N. A. and Lefkovitch, L. P. 2001. Effect of post-harvest management on seed production of creeping red fescue, tall fescue, and Kentucky bluegrass in the Peace River region of north-western Canada. Can. J. Plant Sci. 81: 693-701. A field study in the Peace River region of northwestern Canada evaluated five post-harvest management (PHM) treatments on the seed yield and quality of four grasses, viz. Boreal creeping red fescue (Festuca rubra L. var. rubra), Safari and Tomahawk tall fescue (F. arundinacea … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 8 publications
2
13
0
Order By: Relevance
“…The lack of sensitivity of seed yield of creeping red fescue to various mechanical residue removal procedures is in agreement with previous results (Fairey and Lefkovitch 2001). In that study, a range of postharvest management treatments were applied immediately after seed harvest, and it was concluded that the short period of time between seed harvest and the onset of winter in the study region limits the responsiveness of grass seed crops to a broad range of post-harvest treatments.…”
Section: Seed Yield As Affected By Post-harvest Managementsupporting
confidence: 79%
“…The lack of sensitivity of seed yield of creeping red fescue to various mechanical residue removal procedures is in agreement with previous results (Fairey and Lefkovitch 2001). In that study, a range of postharvest management treatments were applied immediately after seed harvest, and it was concluded that the short period of time between seed harvest and the onset of winter in the study region limits the responsiveness of grass seed crops to a broad range of post-harvest treatments.…”
Section: Seed Yield As Affected By Post-harvest Managementsupporting
confidence: 79%
“…Considering all the above reported results, it is confirmed that, in temperate climates, the ability of developing a high number of tillers during the establishment year (before winter) is a primary requirement for high SY in the following growing season for all perennial grasses (Binek and Mos´, 1992;Heide, 1994;Fairey and Lef kovich, 2001;Martyniak and Pron´czuk, 2003;Gozdowski et al, 2008). It is also confirmed that that the size of tillers at the end of the establishment year is important, as already indicated by Boelt (1999) working with red fescue.…”
Section: Discussionmentioning
confidence: 71%
“…In addition to sowing in pure stands, red fescue may also be undersown in some selected cover crops (intercrop sowing) (Fairey and Lef kovich, 2001). Red fescue seed crops can be established by sowing in pure stands either in the spring or summer.…”
mentioning
confidence: 99%
“…and the Low, Medium and High rotary cultivation treatments produced 1.8-2.6-fold as much seed per panicle as the no-cultivation treatment, with the amount increasing as the intensity of the cultivation increased (Table 5). A similar increase from rotary cultivation, to 165% of the control, was observed in the seed yield of individual panicles of creeping red fescue in another trial in the study region, but panicle density was decreased such that seed yield per unit land area was not increased (Fairey and Lefkovitch 2001). Similarly, in the Pacific Northwest USA, the drop in seed yield of Kentucky bluegrass with increased stand age was not prevented by "gapping" the stand in alternate years although seed yield was increased at lower rates of N fertilizer, seed weight per panicle was increased, and panicle numbers were reduced particularly at higher rates of N fertilizer (Evans and Canode 1971).…”
Section: Resultsmentioning
confidence: 51%
“…*, **, *** Statistically significant at P ≤ 0.05, P ≤ 0.01, and P ≤ 0.001, respectively; NS, not signficant. mental to seed yield because there is insufficient time, between seed harvest and the onset of winter, for the formation and growth of an optimum density of inducible tillers (Fairey and Lefkovitch 2001). CONCLUSIONS 1.…”
Section: Resultsmentioning
confidence: 99%